2019
DOI: 10.1111/cobi.13380
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay to protect cold water corals

Abstract: There is increasing pressure to use currently untapped resources in the deep sea, raising questions regarding ecosystem service trade‐offs in these often unknown areas. We assessed the trade‐offs between protection of cold‐water coral reefs and economic activities, such as fisheries and petroleum extraction, through a survey of a representative sample of the populations of Norway and Ireland. Choice‐experiment surveys were conducted in workshop settings and through the internet. Both survey approaches provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The overall strong preferences held by respondents concerning deep‐seas litter reduction point to greater attention being given to this issue internationally (i.e., supporting efforts to include marine litter in the ongoing BBNJ negotiations) (Tiller & Nyman, 2018). Very few researchers have used stated‐preference methods to investigate the link between nonuse values and policy support for marine habitat conservation in terms of MPAs (e.g., Aanesen et al., 2015; Armstrong et al., 2019b; Börger et al., 2014), and none of the earlier studies relate to high‐seas closures. We identified public preferences not only for existence values of deep‐seas species but also for marine conservation measures (i.e., MPAs), the latter of which is often viewed as important for protecting marine biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall strong preferences held by respondents concerning deep‐seas litter reduction point to greater attention being given to this issue internationally (i.e., supporting efforts to include marine litter in the ongoing BBNJ negotiations) (Tiller & Nyman, 2018). Very few researchers have used stated‐preference methods to investigate the link between nonuse values and policy support for marine habitat conservation in terms of MPAs (e.g., Aanesen et al., 2015; Armstrong et al., 2019b; Börger et al., 2014), and none of the earlier studies relate to high‐seas closures. We identified public preferences not only for existence values of deep‐seas species but also for marine conservation measures (i.e., MPAs), the latter of which is often viewed as important for protecting marine biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…High seas are often described as a free for all involving a tragedy of the global commons because no single nation has sole responsibility for their management (White & Costello, 2014). Despite the growth in international bodies (e.g., United Nations International Seabed Authority, Regional Fisheries Management Organizations, and the International Maritime Organization) and international conventions (e.g., Convention on Biological Diversity and Convention on Migratory Species) that govern human activities associated with high seas, their ecosystems are facing risks resulting from anthropogenic activities (Armstrong et al., 2019a). Temperature change, ocean acidification, fishing, pollution, and oil and gas activities have negative impacts on deep‐seas ESs, where biodiversity, habitat, and fish and shellfish are most at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Third, mitigation of the impacts of climate change. As a natural coastal protection system, coral reefs can mitigate the impact of storms and waves on coastal areas, thereby reducing the impact of sea level rise and extreme climate events on coastal areas caused by climate change (Armstrong et al, 2019). In summary, coral reefs play an important role in the global carbon cycle and carbon emissions.…”
mentioning
confidence: 99%
“…These technologies involve theories and methods related to physics, biology, geography, etc. Some scholars have studied the use of appropriate management methods or management modes to protect coral reefs, Topor et al (2019) believed that promoting fish diversity can enhance the function of coral reefs; Hall et al (2022) believed that banning harpoon fishing can improve the protection effect of coral reefs; Nolan et al (2021) created a reserve quality score to determine the priority of coral reef space protection; Armstrong et al (2019) analyzed the behavioral level of how much people are willing to pay for the protection of coral reefs; Hopf et al (2019) believed that nature reserves play an important role in fish populations and fish production in coral reef systems; Yanovski and Abelson (2019) believed that structural complexity enhancement is a restoration tool for coral reefs. These management methods cover related theories such as biodiversity, protected areas, and ethology.…”
mentioning
confidence: 99%
“…evaluated the world's largest concentration of cold-water coral and identified high average WTP (range of €274 to €287) among Norwegian participants for the size of the protected area, attractiveness for oil/gas and fisheries activities, and importance as a habitat for fish. The most recent beingArmstrong et al (2019) who found that the Norwegians and Irish were willing to pay average values of NOK341 and NOK424 for a small and large increase in protected areas respectively. Norwegians expressed a stronger preference for the pure existence value of cold water corals than the Irish, and the Irish were also less willing to trade-off industrial activities than the Norwegians.Assuming the discrete distribution of attribute parameters as a way of latently clustering the population,Kermagoret et al (2016) andBörger and Hattam (2017) have studied marine offshore areas.…”
mentioning
confidence: 99%